UPAYA PENANGGULANGAN KENAKALAN PESERTA DIDIK DI MADRASAH TSANAWIYAH NEGERI SUNGAYANG KABUPATEN TANAH DATAR - Yulmawati Yulmawati (IAIN Batusangkar, 2016)
Based on the achievements of State Islamic Secondary School Sungayang it also had many violations were done by student as seen in the students’ case book in the academic year 2015/2016. The violation was only related to discipline, but it prohibits the school’s progress. This research was aimed at describing the response of State Islamic Secondary School Sungayang toward students’ delinquency. This study was qualitative case study by applying observation, interview and documentation as instruments on collecting data. The primary data in this study were Vice Head of Students, Guidance and Counseling Teacher and students. The results revealed that the efforts to tackle students’ delinquency was understanding the forms of delinquency committed by students. There were high, medium and low delinquency. The students’ delinquency might come from family and school factor. The efforts on overcoming studetns delinquency were preventive, curative and rehabilitation. On the preventive, the school did socialization to the parent and the community. On the curative, the school gave the punishment based on the type of delinquency. On the rehabilitation, the school did direction and education of a noble human being. While the obstacles encountered were many parents ignore their children; the rule did not correspond to the current situation; and the students nowadays at the age of transition of delinquency.Keywords: The Students’ Delinquency, State Islamic Secondary School, Sungayang, Tanah Datar